2018
DOI: 10.4081/ija.2018.1246
|View full text |Cite
|
Sign up to set email alerts
|

Split nitrogen sources effects on nitrogen use efficiency, yield and seed quality of safflower (Carthamus tinctorius L.)

Abstract: The effects of nitrogen (N) on crop yields have historically been assessed with field trials, but selection and use of the best sources and optimal timing N applications have a significant role in realizing the maximum potential of oilseeds quality and quantity. This study was conducted to determine the combine effects of N sources [ammonium nitrate (AN), ammonium sulphate (AS), sulphur coated urea (SCU), and urea (U)] and split N fertilisation [(1/4,3/4,0), (1/3,1/3,1/3), (1/2,1/2,0), and (1/3,2/3,0)] on saff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 29 publications
(34 reference statements)
0
3
0
Order By: Relevance
“…[78][79][80] The irrigation water and fertilizers should be applied at the proper time and in appropriate amounts to get the higher WUE and NUE with optimal grain yield. It highlighted that applying fertilizer in the three-split application 81 rather than two split applications can be beneficial to obtain optimum grain yield. [81][82][83][84] We also found that grain yield and NUE did not always increase with enhancing the amounts of fertilizers, which is agreed well with the previous study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[78][79][80] The irrigation water and fertilizers should be applied at the proper time and in appropriate amounts to get the higher WUE and NUE with optimal grain yield. It highlighted that applying fertilizer in the three-split application 81 rather than two split applications can be beneficial to obtain optimum grain yield. [81][82][83][84] We also found that grain yield and NUE did not always increase with enhancing the amounts of fertilizers, which is agreed well with the previous study.…”
Section: Discussionmentioning
confidence: 99%
“…It highlighted that applying fertilizer in the three-split application 81 rather than two split applications can be beneficial to obtain optimum grain yield. [81][82][83][84] We also found that grain yield and NUE did not always increase with enhancing the amounts of fertilizers, which is agreed well with the previous study. 85,86 Furthermore, the lower dose of nitrophos (70% of the farmer's practice in our experiment) and deficit irrigation (60% of ETc) resulted in minimum yield attributes, grain yield, WUE, and NUE.…”
Section: Discussionmentioning
confidence: 99%
“…In modern crop fertilization techniques, foliar feeding takes a wide range of researchers' attention. Therefore, the foliar application of plant nutrients, especially micro-nutrients, has become an effective way to increase production and improve the quality of field crops (Talebbeigi et al, 2018).…”
Section: Introductionmentioning
confidence: 99%